IMPLEMENTASI MANAJEMEN ENGLISH AS SECOND LANGUAGE SEKOLAH TUNAS MEKAR INDONESIA LAMPUNG - Aries Pratama; Supomo Kandar; Sulton Djasmi (Program Studi Magister Manajemen Pendidikan)
The aim of the research was to describe the implementation of English as Second Language (ESL) Management in Sekolah Tunas Mekar Indonesia. This reasearch focused on some points, which were: 1) The Planning of ESL Management, 2) The Implementation of ESL Management, and 3) The Controlling of ESL Management. Qualitative research method which involved data collection techniques through observation, documentation and interviews. The data sources were the leader of ESL Division and all executives. Data analysis is done by interactive method. The results of research were: 1) The Planning of ESL Management was involving all leaders of divisions. 2) The Implementation of ESL Management ran based on the plan formulated. The actuating process performed thoroughly in all divisions, as expected in Kindergarten and Elementary School Level. 3) The Controlling of ESL Management in Sekolah TMI involved all layers of school in supervising, assessing, and giving feedback to the school.Tujuan penelitian ini adalah untuk mendeskripsikan pelaksanaan Manajemen ESL di Sekolah Tunas Mekar Indonesia. Fokus penelitian ini adalah Perencanaan Manajemen ESL, Implementasi Manajemen ESL, dan Pengendalian Manajemen ESL. Metode penelitian kualitatif dengan teknik pengumpulan data melalui observasi, dokumentasi dan wawancara. Sumber data adalah Kepala Divisi ESL dan para eksekutif. Analisis data dilakukan secara interaktif. Hasil Penelitian adalah: 1) Perencanaan Manajemen ESL melibatkan seluruh pimpinan, 2) Implementasi Manajemen ESL berjalan sesuai dengan formulasi perencanaan. Proses pelaksanaan berjalan berjalan secara menyeluruh dan sesuai dengan harapan pada Divisi TK dan SD. 3) Pengendalian manajemen ESL di Sekolah TMI melibatkan seluruh unsur Sekolah TMI dalam proses pengawasan, penilaian dan penciptaan umpan balik. Kata kunci : manajemen inglish as second language